Numerical modelling of gas metal arc joining of aluminium alloy and galvanised steels in lap joint configuration. (18th May 2016) - Das, A.; Shome, M.; Goecke, S.-F.; De, A.
Abstract : Advanced pulsed current gas metal arc based processes are increasingly attempted for the joining of aluminium alloys and galvanised steel sheets. The bead profile and the thickness of the interfacial Fe–Al intermetallic (IMC) layer significantly influence the failure strength of these joints. Although several experimental studies have examined the nature and extent of the IMC phases and consequent joint strength, quantitative efforts to estimate bead profile and the IMC layer thickness as function of process conditions and resulting heat input are scarce. We present here for the first time a coupled theoretical and experimental study to estimate the bead profile and Fe–Al IMC layer thickness for joining of galvannealed steel and aluminium alloy sheets in a typical lap joint configuration. The computed values of bead profile and IMC layer thicknesses are validated with the corresponding experimental results.